Positive Relational Management for Healthy Organizations: Psychometric Properties of a New Scale for Prevention for Workers - Di Fabio, Annamaria (Frontiers in Psychology, 2016)
This contribution aims at evaluating the psychometric properties of the Positive Relational Management Scale (PRMS) in a sample of two hundred and fifty-one Italian workers. The dimensionality, reliability, and concurrent validity of the scale were investigated. Confirmatory factor analysis supported a correlated three-dimensional version of the scale, comprising Respect, Caring, and Connectedness. Latent correlations among the dimensions were moderate-to-strong (.44 - .57), but suggestive of the multidimensionality of the scores. In addition, good internal consistency was confirmed. The concurrent validity is good as the Pearson’s correlations between PRMS and measure for social support, life satisfaction, life meaningfulness, and flourishing range from .39 to .52. The results indicate that the PRMS is a valid instrument for measuring positive relational management at work in the Italian context within a positive preventive perspective.